Seismic scale bottomset facies of a mixed carbonate siliciclastic ramp: The Jurassic-Cretaceous Vaca Muerta Formation in the Picún Leufú area, Neuquén basin, Argentina - Paz, Maximiliano (2017)
Fil: Paz, Maximiliano. University of Saskatchewan. Department of Geological Sciences. Saskatoon, Canada